Hakekat Nyanyian Dalam Liturgi: Katekese Liturgi - Yusuf Silaban (Jurnal Magistra, 2024)
The research is dedicated to the 60th anniversary of the Sacrosanctum Concilium (1963-2024). It is a special moment to reflect on the mystery of Crist celebrated in the liturgy. The main issue we are going to present is the relationship between song and liturgy and its function in liturgical celebrations. A song is a liturgical song when enters into the liturgy; it becomes part of the liturgy and takes a part in the purpose of the liturgy: to glorify God and sanctify the people of God. Liturgical songs lead them into the mystery that they are going to celebrate; as an accompaniment to ritual actions, adding the splendor and beauty of the celebration, or explaining and meditating the rite. Therefore, the text of the liturgical songs must be compatible with both the theological teachings and the actual celebration. It means liturgical songs are reserved to accompany liturgical celebrations only.